Outcome of conservative therapy of Adolescent Idiopathic Scoliosis (AIS) with Chêneau-Brace - Pepke, Wojciech; Morani, William; Schiltenwolf, Marcus; Bruckner, Thomas; Renkawitz, Tobias; Hemmer, Stefan; Akbar, Michael (Journal of Clinical Medicine, 2023)
Chêneau-brace (C-Brace) is a potential tool for the treatment of adolescent idiopathic scoliosis (AIS) with a Cobb angle between 20° and 45° for the primary curve. The aim of the present study was (1) to estimate study cohorts with C-brace therapy success and therapy failure and (2) to analyze possible factors that influence the therapy outcome. Seventy-eight patients with AIS were assessed before the initiation of C-brace treatment. Each patient underwent radiography examinations before the brace, in-brace, and at the therapy end. Cobb angle was considered as increased when the value at the end of therapy was increased more than 5° (Δ > 5°), unchanged—when the value was unchanged within ± 5° and decreased- when the value was decreased more than 5° (Δ < −5°). The study cohort was stratified due to curve topography in the thoracic, thoracolumbar, and lumbar scoliosis groups. Global analysis revealed no statistically significant modification of the Cobb angle (Cobb angle pre-brace vs. Cobb angle post-brace: 30.8° ± 8.2 vs. 29.3° ± 15.2, p = 0.26). However, at the end of C-brace therapy, the primary Cobb angle was decreased by more than 5° in 27 patients (35%), unchanged (Δ within the range of ±5°) in 36 patients (46%), and increased more than 5° in 15 patients (19%). Sub-group analysis due to curve topography and skeletal maturity has shown higher rates of brace therapy failure in thoracic curves and in younger patients (Risser grade 0). Patients with higher Cobb angle correction with C-brace had lower rates of therapy failure. The C-brace can be useful for the prevention of scoliotic curve progression in patients with AIS. However, many factors influence the therapy effect.